2014
DOI: 10.1055/s-0033-1363465
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Resolution Ability in Students with Dyslexia and Reading and Writing Disorders

Abstract: Introduction The Gaps-in-Noise (GIN) test assesses the hearing ability of temporal resolution. The development of this ability can be considered essential for learning how to read. Objective Identify temporal resolution in individuals diagnosed with reading and writing disorders compared with subjects with dyslexia. Methods A sample of 26 subjects of both genders, age 10 to 15 years, included 11 diagnosed with dyslexia and 15 diagnosed with reading and writing disorders. Subjects did not display otologic, neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
2
15
1
3
Order By: Relevance
“…This finding corroborates other studies that show that children with learning difficulties present changes in their temporal auditory processing (6,11,(20)(21)(22) . Parents reported a high number of behavioral manifestations, such as hyperactivity/inattention, conduct problems, peer relationship problems, and emotional symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding corroborates other studies that show that children with learning difficulties present changes in their temporal auditory processing (6,11,(20)(21)(22) . Parents reported a high number of behavioral manifestations, such as hyperactivity/inattention, conduct problems, peer relationship problems, and emotional symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…According to the literature, temporal ordering and resolution abilities affect the perception and understanding of human speech, therefore constituting a prerequisite for language abilities (5) . A change in auditory perception can cause problems in the development of speech and language, as well as in the learning and socialization of children (6) . A longitudinal study conducted with 236 German children, who were monitored for twenty months, found that auditory temporal order thresholds have a causal influence on literacy development (7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between the Word-pseudoword Reading Competence (WPRC) test and SATO skills showed that most of the schoolchildren analyzed presented normal and adequate results, respectively, in both assessments. Despite the absence of statistical significance, this finding corroborates the literature (13) , because impairments in auditory processing are often associated with difficulties in reading, writing, and learning (2,9,(13)(14)(15) . To this extent, the present data reinforce the importance of the hearing-language interaction.…”
Section: Discussionsupporting
confidence: 87%
“…Temporal auditory processing is related to the ability to recognize, identify, and order acoustic stimuli during a given time, according to the order in which they were presented (6) . Based on the fact that this auditory ability is essential for speech and language comprehension, its inadequacy may reflect difficulties in spelling and coding/decoding both words and phrases (6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%